Design and Implementation of a Software Platform for a new generation of Measurement Instruments - Persson, Jim (My University, 2009)
Ranatec Instrument AB designs and develops measurement instruments for use in high performance applications such as radars. These instruments rely on a combina- tion of custom hardware and software in order to function properly. This thesis will present a software platform for measurement instruments that is designed to solve the problems with the old platform, which was severely limited in both capabilities and performance. The new platform utilizes Linux as the operating system kernel, coupled with a set of userspace utilities from several sources in the Open Source and Free software communities as well as custom software, to build a robust, flexible and efficient software platform. Apart from being a solid operating system that can run custom applications, the platform also include system daemons for user interaction and control as well as an update framework that enables fail-safe and secure software updates initiated by a technician in the field or remotely over the Internet or LAN. The new system offers greatly improved performance and hardware support compared to the previous platform. The case study in this thesis will be a noise figure meter instrument designed to measure signal-to-noise ratios in radars, but the platform is not limited to this application alone.
Keywords: Datorteknik; Computer Engineering